MicroRNA-484 is more highly expressed in serum of early breast cancer patients compared to healthy volunteers - Zearo, Silvia (BioMed Central, 2014)
BACKGROUND: Previous studies have profiled breast cancer compared to normal breast tissue and identified differentially expressed microRNAs (miRNAs). These miRNAs are then assessed in serum of breast cancer patients compared to healthy volunteers. MiRNAs in serum however do not always reflect what is in tissue and important serum miRNAs may be missed. PCR arrays were therefore performed on serum samples from breast cancer patients compared to healthy volunteers with the aim of identifying circulating miRNAs that are more highly expressed in serum from early breast cancer patients compared to controls. METHODS: Taqman low density array (TLDA) cards were used to profile serum miRNAs in a discovery cohort of serum from 39 early breast cancer patients compared to 10 healthy volunteers. The results were confirmed in a validation cohort of serum from 98 early breast cancer patients compared to 25 healthy volunteers using customized qPCR plates. RESULTS: Seventeen miRNAs were found to have significantly higher levels in breast cancer serum compared to serum of healthy volunteers in the discovery cohort. Fourteen of these miRNAs were studied in the validation cohort and serum miR-484 was found to be at a significantly higher level in breast cancer serum compared to healthy volunteers. CONCLUSION: In this study, we found that miR-484 is significantly differentially expressed in serum of early breast cancer patients compared to healthy volunteers. We did not however find any correlation between miR-484 levels with histopathological parameters of the breast cancers. With further studies, miR-484 may prove useful as an adjunct to mammography for detection of early breast cancer.